2015
DOI: 10.1017/s1368980014003255
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and non-compliance in a family-led weight-management programme for obese Pacific children

Abstract: Objective: To explore factors influencing participation and attrition in a family-led weight-management programme for obese Pacific children. Design: Qualitative study used bilingual in-depth interviews at exit and end of an 8-week weight-management programme. Setting: New Zealand. Subjects: Forty-two parents/primary caregivers of obese children who were randomised in the intervention weight-management programme. Results: Programmatic factors that enhanced retention included: simultaneous delivery to both chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 40 publications
1
32
0
2
Order By: Relevance
“…Screening of titles and abstracts resulted in 78 potentially eligible studies. Of these, 13 peer‐reviewed journal articles met the inclusion criteria . Qualitative methods were employed in five of the studies included (Table ), quantitative methods in six (Table ) while two studies used mixed‐methods to achieve their aim (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening of titles and abstracts resulted in 78 potentially eligible studies. Of these, 13 peer‐reviewed journal articles met the inclusion criteria . Qualitative methods were employed in five of the studies included (Table ), quantitative methods in six (Table ) while two studies used mixed‐methods to achieve their aim (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported on the modifiable factors influencing attendance (e.g. programme location and staff) . Out of these, eight explored the reasons behind both initial and continued attendance, while Rice et al reported solely on the factors influencing initial attendance and Gronbaek et al reported exclusively on continued attendance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most promising aspect of this alternative research strategy is that it is relevant to research participants seeking immediate advice and gives hope to families living in impoverished circumstances, that solutions lie within their own communities. This may be particularly effective for Pacific people and other ethnic minority groups, who value role modelling from families with similar circumstances and backgrounds 40 …”
Section: Discussionmentioning
confidence: 99%
“…Focus group interviews for a YMCA family weight management program for elementary school age children, as well as for weight management programs in other settings, show that families prefer interactive sessions including exercise and cooking demonstrations [9,27,28]. Most YMCAs in the United States, including the Rochester Area Family YMCA in Rochester, MN, have adopted a set of Healthy Eating and Physical Activity (HEPA) standards [29].…”
Section: Introductionmentioning
confidence: 99%